Gelfand pair associated with a hoph algebra and a coideal - Chapovsky, Yu. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We consider a pair of a compact quantum group and a coideal in its dual Hopf *-algebra and introduce the notions of Gelfand pair and strict Gelfand pair. For a strict Gelfand pair, we construct two hyper-complex systems dual to each other. As an example, we consider the quantum analog of the pair (U(n), SO(n)).